PENGARUH PENGALAMAN PELANGGAN DAN KEPUASAN PELANGGAN TERHADAP MINAT WISATAWAN BERKUNJUNG KEMBALI KE PULAU PAHAWANG LAMPUNG - Ranti Puspitasari; Suprihatin Ali (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This research aims to determine the influence of customer experience and customer satisfaction on tourists' intentions to revisit Pahawang Island, Lampung. This research uses a method quantitative. The population of this research is Lampung tourists who have visited Pahawang Island. The sampling technique used purposive sampling with a sample size of 100 respondents. Data was obtained through a Google Form questionnaire and distributed online via the WhatsApp, Twitter, Line and Instagram applications. The analysis techniques used include validity tests, reliability tests, multiple linear regression, t tests, F tests, and R2 tests using computational calculations from the SPSS 26 (Statistical Package for Social Science) program. The results of this research are that the variables customer experience and customer satisfaction have an influence on tourists' revisit intentions to Pahawang Island, Lampung. The recommendation suggested by the author to the management of Pahawang Island, Lampung, it is important for the management of Pahawang Island to maintain the quality of cleanliness and sustainability of the beach area and to be wiser in determining prices so that they are affordable for tourists. Apart from that, price increases must remain within reasonable limits and be acceptable to both parties without anyone feeling disadvantaged. As well as improving the quality of products and services so that tourists can tolerate competitors who will arrive in greater numbers and become more attractive in the future.